Experimental Workshop : Japan 1951-1958. - Annely Juda Fine Art, London; Obinata, Kinichi; Otani, Shogo; Reichardt, Jasia; Takigucchi, Shuzo; Yamaguchi, Katsuhiro (London : Annely Juda Fine Art, 2009)
Akiyama, Kuniharu ; Fukushima, Hideko ; Fukushima, Kazuo ; Imai, Naoji ; Kitadai, Shozo ; Komai, Tetsuro ; Otsuji Kiyoji ; Yamaguchi, Katsuhiro ; Sato, Keijiro ; Sonoda, Takahiro ; Suzuki, Hiroyoshi ; Takiguchi Shuzo ; Takemitsu, Toru ; Yuasa, Joji
Experimental Workshop - A Chronological History [9 p.], biog. [7 p.]
Engels
Experimental Workshop: Japan 1951-1958, Annely Juda Fine Art, London, 29 october -18 december 2009
Exhibition. Experimental Workshop : Japan 1951-1958. London. Annely Juda Fine Art London. 2009-10-29. 2009-12-18
kunstcatalogus
Keywords: Experimental; Japan